Qualitative And Comparisonal Evalution of Dimentionas of University Professors through 360 Digree Thechnique - Jafari, Mostafa; Afshari, Mina (Advances in Social Sciences Research Journal, 2018)
New days , there are many evolution in knowledge of management , being of system of available is unavoidable ,that absence of it is in dimension of different "s organization ,level of management ,personal as one of banner of malady "s organization . Operation assess pattern degree 360 is signal of wind age operation. And in it is main development of lead quality & development management. This process is perfect cycle, that it is windward extract all of person (supervisors, subalterns, and, coworkers) in different ways of lead & his management & operation endow uniformly and amiable. Target of this research professor operation examination with degree